2021
DOI: 10.1039/d0sc02812f
|View full text |Cite
|
Sign up to set email alerts
|

Delocalization tunable by ligand substitution in [L2Al]ncomplexes highlights a mechanism for strong electronic coupling

Abstract: Ligand-based mixed valent (MV) complexes of Al(III) incorporating electron donating (ED) and electron withdrawing (EW) substituents on bis(imino)pyridine ligands (I2P) have been prepared. The MV states containing EW groups are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…62 and 53%, respectively, of the predicted values. These fall within the range associated with recent species assigned as either valence-trapped with very strong coupling (Robin-Day class II−III) 65,67,68 or completely valence-delocalized (Robin-Day class III). 67−69 The moderate solvatochromism of 3b 2+ , 39,67,70 and the two separate ν(C�C) bands in the IR spectrum of 3c 2+ preclude a completely valence-delocalized description.…”
Section: ■ Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…62 and 53%, respectively, of the predicted values. These fall within the range associated with recent species assigned as either valence-trapped with very strong coupling (Robin-Day class II−III) 65,67,68 or completely valence-delocalized (Robin-Day class III). 67−69 The moderate solvatochromism of 3b 2+ , 39,67,70 and the two separate ν(C�C) bands in the IR spectrum of 3c 2+ preclude a completely valence-delocalized description.…”
Section: ■ Introductionsupporting
confidence: 65%
“…62 and 53%, respectively, of the predicted values. These fall within the range associated with recent species assigned as either valence-trapped with very strong coupling (Robin-Day class II–III) ,, or completely valence-delocalized (Robin-Day class III). The moderate solvatochromism of 3b 2+ , ,, and the two separate ν(CC) bands in the IR spectrum of 3c 2+ preclude a completely valence-delocalized description. , Therefore, 3b / c 2+ are conservatively assigned as valence-trapped complexes exhibiting moderate ( 3c 2+ ) to strong ( 3b 2+ ) coupling (Robin-Day class II, perhaps approaching class II–III). For 3a 2+ , similar behavior to 3b 2+ is likely based both on the similar intensity of the IVCT bands (Table ) and on the apparent valence delocalization of 3a 2+ on the IR timescale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactivity and electrochemistry of iminopyridine complexes of Al and Ga have been studied by Berben et al 66–69 and have been reviewed elsewhere. 70 It has been shown that a series of octahedral group 13 complexes of 2,6-bis{1-[(2-methoxyphenyl)imino]-benzyl}pyridine (I 2 P, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with prior work showing metalloaromatic character in Al III and Ga III complexes of I 2 P, 41,42 and work where Class III mixed-valency is supported by Al III and Ga III ions that bridge two I 2 P ligands. 35,43 Transition element analogs of these two compound classes do not have the same electronic properties.…”
mentioning
confidence: 99%